CRACK PROPAGATION CHARACTERISTICS OF SINGLE LAP JOINT WITH BLIND RIVET - Harza Irawan, Yusvari
Indonesia through PT. Dirgantara Indonesia is trying to contribute in the field of air transportation, especially remote areas in Indonesia. To be able to compete with other pioneering aircraft manufacturers, reliable aircraft products are needed. Structural engineering has two important objectives, namely to increase Fatigue life, and predict the fatigue life of the connection structure. One way to increase fatigue lifetime of a connection is to provide residual Stress. In this study a simulation of the process of tracking is carried out to obtain the residual Stress generated and a crack propagation simulation is carried out to determine the characteristics of crack propagation from the use of blind rivets.